Questions and answers, elements of banking - Ogubunka, Uju M.; Omojola, Akin (Lagos, Nigeria : Rhema Enterprises, 2002)
The book shows simple and best ways to answer questions on elements of banking and provides a pre-examination ‘last minute’ revision made easy book.
lje 03/08/13
Loan
Keywords: Banks and banking